PENGARUH FAKTOR PAJAK DAN NON PAJAK TERHADAP KEBIJAKAN HUTANG (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode Tahun 2010-2014) - Risa Rahmawati, 12.05.52.0178; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2016)
The purpose of this research is to examine The Effect of CTR, Asset Structure, Profitability, Firm Size, Firm Growth, and Institusional Ownership on Debt Policy. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (IDX) in the period 2010-2014 a total of 155 companies. Methods of analysis of this study uses multiple regression. The result of this research shows that: (1) CTR has negative and not significant effect on corporate debt policy, (2) Asset Structure has negative significant effect on corporate debt policy, (3) Profitability has negative significant effect on corporate debt policy, (4) Firm Size has positive and not significant effect on corporate debt policy, (5) Firm Growth has positive significant effect on corporate debt policy, (6) Institusional Ownership has negative significant effect on corporate debt policy.Keywords: CTR, Asset Structure, Profitability, Firm Size, Firm Growth, Institusional Ownership, Debt Policy